Hepatoprotective Effect of Azolla microphylla on Isoproterenol-induced Rats and the Identification of Active Compound through HPTLC and GC-MS Analysis - Bhaskaran, Sreenath K.; Kannappan, Poornima; Muneeswari, Perumalsamy; Madathil, Sri R. (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2021)
Aim: To study the pretreatment effect of ethanolic extract of Azolla microphylla (EAM) on rat liver induced with Isoproterenol (ISO) and to identify the phytochemicals present in EAM using HPTLC and GC-MS techniques. Materials and Methods: 42 male Wistar rats were divided into 7 groups. Rats were pre-treated with EAM (250 and 500 mg/kg bw) orally for 28 days and induced with ISO (85 mg/kg; intra-peritoneal) on the 29th and 30th days. Blood and liver samples were collected from all the rats on the 30th day for biochemical and histopathological observations. HPTLC and GC-MS analyses of EAM were done using the standard protocols. Results: The ISO-induced group of rats displayed a significant decrease in the hepatic tissue level and activities of total protein and Aspartate Transaminase (AST), Alanine Transaminase (ALT), Alkaline Phosphatase (ALP) enzymes, respectively. Moreover, a significant decline in enzymatic and non-enzymatic antioxidants levels was spotted in the same group. However, EAM pretreatment for 28 days significantly protected the rat liver from the aforementioned alterations. Nevertheless, histopathological analysis revealed central vein dilation, necrosis, and infiltration of inflammatory cells in the ISO-induced group, wherein, EAM pretreatment significantly protected the hepatocytes from the above-mentioned changes indicating its antioxidant and cytoprotective potential. HPTLC analysis displayed the presence of flavonoids. The GC-MS analysis confirmed the presence of quercetin in EAM. Conclusion: The overall results suggest that EAM pretreatment possesses an ameliorative effect against the ISO-induced oxidative damage in the rat hepatocytes.
Keywords: quercetin